2020
DOI: 10.1007/s10270-020-00815-4
|View full text |Cite
|
Sign up to set email alerts
|

Claimed advantages and disadvantages of (dedicated) model transformation languages: a systematic literature review

Abstract: There exists a plethora of claims about the advantages and disadvantages of model transformation languages compared to general-purpose programming languages. With this work, we aim to create an overview over these claims in the literature and systematize evidence thereof. For this purpose, we conducted a systematic literature review by following a systematic process for searching and selecting relevant publications and extracting data. We selected a total of 58 publications, categorized claims about model tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Nowadays, however, such claims have two main flaws. First, as discussed by Götz et al, there is a lack of actual evidence to have confidence in their genuineness [2]. Second, we argue that most of these claims emerged together with the first MTLs around 15 years ago.…”
Section: Context and Motivationmentioning
confidence: 55%
See 2 more Smart Citations
“…Nowadays, however, such claims have two main flaws. First, as discussed by Götz et al, there is a lack of actual evidence to have confidence in their genuineness [2]. Second, we argue that most of these claims emerged together with the first MTLs around 15 years ago.…”
Section: Context and Motivationmentioning
confidence: 55%
“…In the literature, many advantages are ascribed to model transformation languages, such as better analysability, comprehensibility or expressiveness [2]. Moreover, model transformation languages aim at abstracting from certain recurring aspects of a model transformation such as traversing the input model or creating and managing trace information, claiming to hide complex semantics behind a simple and intuitive syntax [1,[3][4][5].…”
Section: Context and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, empirical research on usage, advantages, and disadvantages of model transformation languages and corresponding tools is relatively scarce (Götz et al 2020) as works similar to the empirical studies by Hutchinson et al (2011) and Liebel et al (2018) on model-based engineering in general are still missing. Such empirical studies could influence the research in the area of model transformations and may, consequently, positively affect the adoption of model transformations in industrial practice (Burgueño et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Such empirical studies could influence the research in the area of model transformations and may, consequently, positively affect the adoption of model transformations in industrial practice (Burgueño et al 2019). Götz et al (2020) have identified 15 different categories of advantages and disadvantages of model transformations in their recent Systematic Literature Review (SLR). One of these 15 categories is the execution performance of model transformation.…”
Section: Introductionmentioning
confidence: 99%